PASSPORT-G AUTHENTICATION METHOD BASED ON VAPOR-MARKBEARER’S PHOTO - Zeydan, Hiba Zuhair (Al-Nahrain Journal of Science, 2009)
This research proposes a simple method for issuer’s authenticity verification of the Iraqi new passport form that is publicly named as (passport-G). This authentication method is based on a digital watermarking technology that is named as (vapor-mark), and it involves two phases: the embedding phase and the authentication phase. During the embedding phase, a reference number is embedded as a watermark in a specific location entire the passport bearer’s photo. This reference number and its embedding location are derived and encoded from the issuing authentication data such as: the date of issue, the date of expiration, and the passport number. During the authentication phase, the passport is digitally scanned and the embedded reference number is extracted from the bearer’s photo. Then, a verification algorithm is applied to compare the extracted reference number with that number derived from the printed issuing authentication data. If they are identical, then the passport-G is said to be authentic. Otherwise, an unauthorized passport-G reproduction or forgery is detected.